Alcuni spunti di originalità del contributo di Giuseppe Toniolo nella prospettiva economico-aziendale (Società e diritti, 2022)
The author discusses two aspects of the figure of Giuseppe Toniolo: the critique to the positivistic methodological approach that dominates the economic science of his time; the second is the centrality attributed to the figure of the entrepreneur in society and the belief that he or she should possess moral qualities that go hand in hand with the growth of collective welfare.